Time-activity Budget of the Snowy Sheathbill (Chionis albus) Wintering at a Sea Lion (Otaria flavescens) Haul-out in Argentina - Hernandez, Maximiliano Manuel; Beron, Maria Paula; Zumpano, Francisco; Giardino, Gisela Vanina; Seco Pon, Juan Pablo (Waterbirds)
This work aims to provide information regarding the behavioral ecology of the least studied of the two sheathbill species, the Snowy Sheathbill (Chionis albus), wintering in northern Argentina in a male South American Sea Lion (Otaria flavescens) haul-out. Data about bird abundances and time allocated to behaviors was gathered during the final stage of three consecutive non-breeding seasons. Significant differences were found in the abundance between and within seasons. Overall, sheathbills allocated most of their time to foraging, followed by resting and self-maintaining, with the least of the time allocated to agonistic behaviors. The results obtained by the authors demonstrated that the Snowy Sheathbill recurrently used the local sea-lion haul-out as a foraging ground, with steady numbers throughout the non-breeding seasons. Fil: Hernandez, Maximiliano Manuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Beron, Maria Paula. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Zumpano, Francisco. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. Universidad Nacional de Mar del Plata. Facultad de Ciencias Exactas y Naturales. Instituto de Investigaciones Marinas y Costeras; Argentina Fil: Giardino, Gisela Vanina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mar del Plata. Instituto de Investigaciones Marinas y Costeras. ...